2014
DOI: 10.12720/jomb.3.4.306-310
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Functionalized Low Density Polyethylene/Polyaniline Nano Fiber Composite

Abstract: Nano composite based on polyaniline (PANI) nano fibers filler and chromic acid functionalized low density polyethylene (LDPE) matrix with biocompatibility and low percolation threshold value was prepared via twin screw extrusion process. Density measurement, Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Electron Microscopy (FESEM), Energy-dispersive X-ray spectroscopy (EDX), X-ray crystallography (XRD), Brunauer, Emmett and Teller analysis (BET), Thermo Gravimetric (TGA), Differential Scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The ratio of the nanoclay powder to the polymer powder in the mix of the nanocomposite was 5% by weight. This ratio is the most trusted ratio for producing clay/polymer nanocomposite based on the previous studies of the academics and companies , Fouad H. 2001, Gilman W 1999, 2011, Haruguchi K 2002, Hasmulkh 2006, Kazimi 2014, Kornamaa X. 2001, Lebaron P. 1999, Lili C. 2008, Meneghetti P. 2005, Okada A.…”
Section: Nanocomposite Processingmentioning
confidence: 95%
See 3 more Smart Citations
“…The ratio of the nanoclay powder to the polymer powder in the mix of the nanocomposite was 5% by weight. This ratio is the most trusted ratio for producing clay/polymer nanocomposite based on the previous studies of the academics and companies , Fouad H. 2001, Gilman W 1999, 2011, Haruguchi K 2002, Hasmulkh 2006, Kazimi 2014, Kornamaa X. 2001, Lebaron P. 1999, Lili C. 2008, Meneghetti P. 2005, Okada A.…”
Section: Nanocomposite Processingmentioning
confidence: 95%
“…Clay properties make clay particles convenient for reinforcing polymers for developing new composite with enhanced properties since polymers are thermoplastic, hydrophobic and organic materials. But mixing and processing step of nanoclay and polymer to manufacture nanocomposite faced several difficulties such as homogeneity, nanoclay distribution, particles orientation, defects, voids and air bulbs, particle agglomeration, debonding between nanoclay and polymer, exfoliation and intercalation , Fouad H. 2001, Gilman W 1999, 2011, Haruguchi K 2002, Hasmulkh 2006, Kazimi 2014, Kornamaa X. 2001, Lebaron P. 1999, Lili C. 2008, Meneghetti P. 2005, Okada A.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Polymeric composite systems containing PANI are established as having several advantages including the improvement of the processability and fairly good mechanical properties as well as good conductivity . Some studies used PANI as filler rather than as matrix, and it was confirmed that the reinforcement of PANI in a polymer matrix enhanced the physical properties because it is able to create a different phase relative to the matrix material and conductive polymer . Laska et al .…”
Section: Introductionmentioning
confidence: 99%